Synthesis and Characterization of Nano-Particles Based Magnetorheological Fluids for Brake - Chiranjit Sarkar (Japanese Society of Tribologists, 2015)
Magnetorheological (MR) fluids, to be used as brake friction materials, must have high heat transfer rate to dissipate the heat generated during the braking action. The aim of this manuscript is to synthesize MR fluids with nano-silver and nano-copper particles to increase the heat transfer rate and characterize the demagnetizing effect of those particles on the shear stress of MR fluids. Five different MR fluids, containing a different percentage of silver and copper nano particles, were synthesized. Shear stresses of all five MR fluids were measured using magnetorheometer and the results have been plotted. A flywheel based MR brake experimental setup was developed to analyze the performance of synthesized MR fluids. “T” type thermocouples were used to measure the temperature distribution of the fabricated MR brake. The results of the temperature distribution of brakes containing five synthesized MR fluids have been presented and compared.